Neopterin, Inflammation, and Oxidative Stress: What Could We Be Missing? - Steven P. Gieseg; Gregory Baxter-Parker; Angus Lindsay (MDPI AG, 2018)
Neopterin has been extensively used as a clinical marker of immune activation during inflammation in a wide range of conditions and stresses. However, the analysis of neopterin alone neglects the cellular reactions that generate it in response to interferon-γ. Neopterin is the oxidation product of 7,8-dihydroneopterin, which is a potent antioxidant generated by interferon-γ-activated macrophages. 7,8-Dihydroneopterin can protect macrophage cells from a range of oxidants through a scavenging reaction that generates either neopterin or dihydroxanthopterin, depending on the oxidant. Therefore, plasma and urinary neopterin levels are dependent on both macrophage activation to generate 7,8-dihydroneopterin and subsequent oxidation to neopterin. This relationship is clearly shown in studies of exercise and impact-induced injury during intense contact sport. Here, we argue that neopterin and total neopterin, which is the combined value of 7,8-dihydroneopterin and neopterin, could provide a more comprehensive analysis of clinical inflammation than neopterin alone.